Ᾱthār Wa Tadā’iyyāt Al-Ghazw Al-‘Iraqi li Dawlat Al-Kuwait 1990 wa Daur Al-Munadhdhamāt Al-Dawliyyah fi Mu’ālajatiha - Salama Ali Husein Almesaabi (Insaniyat : Journal of Islam and Humanities, 2018)
The invasion of Kuwait in 1990 resulted in many disastrous effects and negative repercussions on the people and State. It reflected on the Iraqi regime and its people as those effects have been extended to all Arab States and the world at large, where those effects and repercussions have taken on many aspects of political, economic and social. The invasion not only had been effected Kuwait but also broadly in the gulf region. This study aims: firstly to study and analyse the political, economic and social implications as the consequences of the Iraqi invasion over Kuwait; secondly, to elucidate and analyse the effects of the Iraqi invasion of Kuwait on Arab relations; thirdly, to explore on the role of international organizations in addressing the effects of the invasion. The result shows that the invasion has brought to a disastrous schism in the unity of the Arab states and put them left behind in the international stage, and the opening of the area to the Western military presence in the Gulf. The economic loss suffered by the Arab Group reached approximately $1 trillion. The social and psychological effects on society and the individual in Kuwait required long years to be addressed. The international organizations have played a prominent role particularly on recording the file of the prisoners and missing persons, and the compensation is also given to them.DOI: 10.15408/insaniyat.v2i2.7607